Ex utero Electroporation into Mouse Embryonic Neocortex - Branden Nelson (Bio-Protocol, 2013)
This technique allows highly efficient and reproducible transfer of DNA/RNA into the embryonic neocortex of rodents across multiple ages. Ex utero electroporation compliments the more technically difficult in utero electroporation technique by maximizing the number of embryos for available for a given experiment, as well as increasing the variety of constructs used in each experiment, thereby helping to reduce their overall numbers. Ex utero electroporation followed by short term organotypic slice culture of embryonic brain sections allows immediate access to multiple slices for choosing optimal ones for live-cell imaging experiments, and characterization of various NSC manipulations in the intact stem cell niche. (see also “In utero Electroporation of Mouse Embryo Brains” (Ge, 2012); “Organotypic Slice Culture of Embryonic Brain Sections” (Calderon de Anda, 2013). Additionally, ex utero electroporated neocortices can be used for in vitro primary cell cultures with further dissection, dissociation into single cells, and plating on cover slips or in multi-well dishes according to standard techniques: note this procedure can be performed immediately after electroporation, prior to the onset of ectopic gene expression, or after overnight slice culturing to collect just the region of electroporated cells.